Prognostic relevance of UCH-L1 and α-internexin in pancreatic neuroendocrine tumors - Yu-Li Song (Nature Portfolio, 2017)
Abstract Prognostic biomarkers for the pancreatic neuroendocrine tumors are needed. Proteomic study on insulinoma has been rarely reported. We identified the differential expression of proteins between insulinoma and their paired tissues by proteomic analysis, and evaluated the prognostic significance of specific proteins in pancreatic neuroendocrine tumors including insulinoma. The differential expression of select proteins was validated in more than 300 tumors using immunohistochemical staining and western blot. Methylation of UCH-L1 promoter in tumors was examined by methylation specific PCR and validated by sequencing. The concurrent expression of UCH-L1 and α-internexin was correlated with the prognosis in 2 independent collectives of patients with tumors. Sixty-two and 219 proteins were significantly down-regulated and up-regulated in insulinomas, respectively. Demethylation of UCH-L1 promoter was associated with UCH-L1 expression in tumors (p = 0.002). The concurrent expression of UCH-L1 and α-internexin in pancreatic neuroendocrine tumors was significantly associated with better overall survival and disease-free survival in the combination of both cohorts (log rank p = 3.90 × 10−4 and p = 3.75 × 10−5, respectively) and in each of cohorts. The prognostic value of both proteins was also validated in patients with stage II and III tumors (p = 0.017 and p = 0.006, respectively). The proteins UCH-L1 and α-internexin could be independent prognostic biomarkers of pancreatic neuroendocrine tumors.